Música brasileira na liturgia: obra, contexto e produto - Almeida, Márcio Antônio de [UNESP] (2014)
The current academic work seeks to cover the first phase of the liturgical and musical reform that took place after the Second Vatican Ecumenical Council (1962-1965) in Brazil. Among all the initiatives in favor of such reform, Brazilian Music in the liturgy can be found in 1969. Given the process of drafting from the papers presented at the National Meeting of Sacred Music, which took place from 1965 to 1968 and were promoted by the National Commission for Sacred Music of the National Conference of Bishops of Brazil (CNBB), this work constitutes a 'historical fact'. During those meetings, a group of musicians, following prescriptions from the conciliar document on the liturgy Sacrosanctum Concilium dated December 4th 1963, gave an original response to the adaptation of liturgical music to Brazilian culture. After delimitating the subject, three visits were made to the CNBB's Center for Information and Documentation in Brasilia, DF, in order to identify, scan and classify the original texts from each Meeting, available in the collection. The analysis of both published and unpublished papers opened questions about the initial strategies around the Brazilian music in the liturgy, as well as enabling a more contextualized research path. As a result, the arguments presented revealed a conceptual proximity to the Brazilian musical modernism due to recurring quotes from the work of Mário de Andrade, Essay on Brazilian music, in order to support Brazilian music criteria in the liturgy, namely, the national theory on the use of melodic and rhythmic certainties of popular music and the creation of the Brazilian recitative. The research work highlighted singularities in the developing of Brazilian Music in the liturgy in order to characterize it as a starting point for procedures undertaken by CNBB, whose resonance covers training strategies and liturgical-musical materials produced in Brazil, 50 years past